Research of Energy-Storage Regenerative Braking Test System in Urban Rail Vehicle - WANG Jian-pu (机车电传动)
Energy-storage regenerative braking test system in urban rail vehicle with feedback-energy was proposed, structure and running principle of which were introduced, as well as composition of experimental system main circuit and circuit topology of energy storage converter device. Three detail working models and circuit principle were analyzed. With a double closed loop of voltage-current control, supercapacitor energy storage was realized to complete braking energy regeneration. Main technical specifications of energy-storage regenerative braking test system in urban rail vehicle was introduced, and at the same time, detection system was applied for experimental data acquisition and procession. The system had characteristics of energy saving, credibility and high precision.